Internal‐Wave Dissipation Mechanisms and Vertical Structure in a High‐Resolution Regional Ocean Model - Joseph Skitka; Brian K. Arbic; Yuchen Ma; Kayhan Momeni; Yulin Pan; William R. Peltier; Dimitris Menemenlis; Ritabrata Thakur (Geophysical Research Letters)
Abstract Motivated by the importance of mixing arising from dissipating internal waves (IWs), vertical profiles of internal‐wave dissipation from a high‐resolution regional ocean model are compared with finestructure estimates made from observations. A horizontal viscosity scheme restricted to only act on horizontally rotational modes (such as eddies) is introduced and tested. At lower resolutions with horizontal grid spacings of 2 km, the modeled IW dissipation from numerical model agrees reasonably well with observations in some cases when the restricted form of horizontal viscosity is used. This suggests the possibility that if restricted forms of horizontal viscosity are adopted by global models with similar resolutions, they could be used to diagnose and map IW dissipation distributions. At higher resolutions with horizontal grid spacings of ∼250 m, the dissipation from vertical shear and horizontal viscosity act much more strongly resulting in dissipation overestimates; however, the vertical‐shear dissipation itself is found to agree well with observations.